Community Participation in Project Closure principles and Performance of Community Water Supply Projects in Kericho County, Kenya - Korir, Justus (Advances in Social Sciences Research Journal, 2020)
The purpose of this article was to establish the extent to which community participation in project closure principles influences the performance of community water supply projects in Kericho county Kenya. The indicators used included community participation in; project documentation and archiving, procurement closure and bills settlement and project handing over and celebration. The study adopted descriptive survey design and correlation research design. The descriptive survey design was used to describe characteristics of the population being studied whilst a correlational research was used to describe the degree to which variables under the study were related. The target population was 8357 and the sample size was 382. Out of this, 310 positively responded. The sample comprised of households and management committee members. The research instruments included questionnaires, focus group discussion and interview schedules. Stratified proportional sampling and random sampling were used to collect primary qualitative and quantitative data. The data was compiled, given codes and input into SPSS version 25 computer program for statistical analysis and presentation. The study findings showed that community participation in project documentation and archiving (R=0.680, p=0.00<0.05, R2=0.461), procurement closure and bills settlement (R=0.772, p=0.00<0.05, R2=0.595) and project handing over and celebration (R=0.746, p=0.00<0.05, R2=0.554) are significant explanatory variables with respect to project performance at 95% confidence level. Therefore, the study concluded that the community should be encouraged to actively participate more during the project closure process in order to enhance the performance of their community water supply projects.